Dependence of nucleotide substitutions on Ung2, Msh2, and PCNA-Ub during somatic hypermutation - Krijger, Peter H L; Langerak, Petra; van den Berk, Paul C M; Jacobs, Heinz (The Journal of experimental medicine, 2009)
During somatic hypermutation (SHM), B cells introduce mutations into their immunoglobulin genes to generate high affinity antibodies. Current models suggest a separation in the generation of G/C transversions by the Ung2-dependent pathway and the generation of A/T mutations by the Msh2/ubiquitinated proliferating cell nuclear antigen (PCNA-Ub)-dependent pathway. It is currently unknown whether these pathways compete to initiate mutagenesis and whether PCNA-Ub functions downstream of Ung2. Furthermore, these models do not explain why mice lacking Msh2 have a more than twofold reduction in the total mutation frequency. Our data indicate that PCNA-Ub is required for A/T mutagenesis downstream of both Msh2 and Ung2. Furthermore, we provide evidence that both pathways are noncompetitive to initiate mutagenesis and even collaborate to generate half of all G/C transversions. These findings significantly add to our understanding of SHM and necessitate an update of present SHM models.